Serum Sphingosine-1-Phosphate Levels Are Associated With Severity and Outcome in Patients With Cerebral Ischemia. Issue 12 (December 2021) - Schwedhelm, Edzard; Schwieren, Laura; Tiedt, Steffen; von Lucadou, Mirjam; Gloyer, Nils-Ole; Böger, Rainer; Magnus, Tim; Daum, Guenter; Thomalla, Götz; Gerloff, Christian; Choe, Chi-un
Abstract : Background and Purpose: The aim of this study was to examine whether sphingosine-1-phosphate (S1P) levels in patients with acute stroke are associated with stroke severity and outcome. Methods: In a prospective stroke cohort (MARK-STROKE), 374 patients with acute ischemic stroke or transient ischemic attack were enrolled (mean age: 67.9±13.0 years, sex: 64.7% male), and serum-S1P at admission was analyzed with tandem mass spectrometry. In addition to cross-sectional analyses, 79 adverse events (death, stroke, myocardial infarction, rehospitalization) were recorded in 270 patients during follow-up. Regression analyses were adjusted for age, sex, low-density lipoprotein cholesterol, and vascular risk factors. Results were validated in an independent stroke cohort with 219 patients with acute ischemic stroke (CIRCULAS). Results: Low serum-S1P was associated with higher National Institutes of Health Stroke Scale score at admission and with anterior circulation nonlacunar infarcts determined by multivariate regression analyses. During a follow-up of 294±170 days, patients with S1P in the lowest tertile (<1.33 µmol/L) had more adverse events (Kaplan-Meier analysis, P =0.048 for trend). In adjusted Cox regression analysis, the lowest S1P tertile was associated with a worse outcome after stroke (hazard ratio, HR 0.51 [95% confidence interval 0.28–0.92]). Results were confirmed in an independent cohort, ie, low S1P levels were associated with higher National Institutes of Health Stroke Scale, larger infarct volumes and worse outcome after 90 days (β-coefficient: –0.03, P =0.026; β-coefficient: −0.099, P =0.009 and odds ratio 0.52 [0.28–0.96], respectively). Conclusions: Our findings imply a detrimental role of low S1P levels in acute stroke and therefore underpin the therapeutic potential of S1P-mimics. Abstract : Supplemental Digital Content is available in the text.